International Evidence on Recovery from Recessions - Cerra, Valerie (IMF Working Papers; Working Paper, 2009)
Although negative shocks have persistent effects on output on average, this paper shows that macroeconomic policies and the structure of the economy can influence the speed of recovery and mitigate the persistence of the shock. Indeed, monetary and fiscal stimulus and foreign aid can spur a rebound, with impacts that are asymmetrically stronger than in nonrecovery years. Real depreciation and the exchange rate regime also have asymmetric growth effects in a recovery year relative to other years of expansion. Recoveries are more sluggish in open economies, partly because fiscal policy is less effective than in closed economies.